DETERMINANT MODEL OF DISTRICT/CITY GOVERNMENT FINANCIAL PERFORMANCE IN SUMATERA UTARA PROVINCE - Alpi, M. Firza; Ammy, Baihaqi (RADJA PUBLIKA, 2021)
The results showed that Capital Expenditure had no partial effect on Financial Performance, Size of Local Government partially affected Financial Performance, and the Remaining Budget Financing partially affected Financial Performance. Partially, Capital Expenditure, Size of Local Government, and Remaining Budget Financing together have an effect on the Financial Performance of district/city governments in North Sumatra Province. The R-Square value is 0.815 or 81.5%. This shows that the variables of Capital Expenditure, Size of Local Government, and Remaining Budget Financing are able to explain the Financial Performance variable of 81.5%. While the remaining 18.5% is explained by other variables outside the study.